Flyte - Sage, Angie; Zug, Mark (New York Katherine Tegen Books, 2006)
When Princess Jenna is pursued by a dark wizard, it is the apprentice, Septimus Heap, who must save her while enduring such terrors as a night in the Forest with hungry wolverines and carnivorous trees.
Some copies may have mini-disc with Flash video.
009-up.
4-up.
112484
Keywords: Princesses -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy; Fantasy fiction -- Juvenile; Fiction; Juvenile works